2007
DOI: 10.2174/138161207781662957
|View full text |Cite
|
Sign up to set email alerts
|

The Podocyte: a Potential Therapeutic Target in Diabetic Nephropathy?

Abstract: Over the last five years, much work has underlined the important role of the podocyte in the development of diabetic nephropathy. The metabolic and haemodynamic abnormalities of the diabetic milieu act in concert, perhaps via the common effector path of oxidative stress and development of reactive oxygen species, to promote podocyte damage. There is loss of nephrin from the slit diaphragm, increased synthesis of some of the components of the glomerular basement membrane, activation of pro-apoptotic and hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 55 publications
(71 reference statements)
0
36
0
1
Order By: Relevance
“…Podocytes, as highly differentiated terminal cells, combine with slit diaphragms among foot processes to form the outermost layer of the glomerular filtration barrier. The fusion and disappearance of foot processes is one of the initial mechanisms of proteinuria formation [8,9], while urinary protein excretion can aggravate podocyte injury. In this study, HQH reduced proteinuria in ADR rats, simultaneously, significantly alleviated podocyte injury, indicating that proteinuria is closely related to podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes, as highly differentiated terminal cells, combine with slit diaphragms among foot processes to form the outermost layer of the glomerular filtration barrier. The fusion and disappearance of foot processes is one of the initial mechanisms of proteinuria formation [8,9], while urinary protein excretion can aggravate podocyte injury. In this study, HQH reduced proteinuria in ADR rats, simultaneously, significantly alleviated podocyte injury, indicating that proteinuria is closely related to podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…24 Podocyte ROI production is stimulated by hyperglycemia, and signs of podocyte activation such as increased vascular endothelial growth factor production are ameliorated by antioxidants. 25 In diabetes, there are also angiotensin II-mediated increases in podocyte NADPH oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…2 Altered podocyte function occurs early in the development of diabetic nephropathy and can affect cell-cell interactions, attachment to the glomerular basement membrane, and apoptosis. [2][3][4][5][6][7][8][9][10] In humans, COX-2 expression is readily detectable in glomerular podocytes of adults, 11,12 and expression levels have been reported to increase during acute renal allograft rejection. 13,14 Occasional COX-2-positive podocytes are also detectable in adult rats, 15,16 and we have previously reported that in rat models of diabetes there is increased COX-2 expression in podocytes, and also in mesangial cells and macula densa cells, and have shown that COX-2 inhibition can attenuate proteinuria and retard diabetic nephropathy progression.…”
mentioning
confidence: 99%